TEACHER OBSERVATION ASSESSMENT FOR PRIMARY EDUCATION - Reny Rika Puspita; Suyatno Suyatno (Universitas PGRI Semarang, 2020)
Teacher observation is an important but underutilized assessment technique. It is sometimes argued that teachers are unable to make appropriate and dependable assessment judgments from observations of students in natural settings. Handled carefully, teacher observations can provide important evidence for assessment judgments. In some cases, they provide the only way of obtaining evidence about particular learning outcomes, especially those involving practical techniques, performance activities, ‘real life’ projects and group work.